Metode Pengajaran Gastronomi bagi Masyarakat Desa Wisata - Adhitiowasis, Aryo; Malihah, Elly; Andari, Rini (Rumah Jurnal UNEJ, 2022)
The development of tourist villages during the current pandemic is important. Especially areas in Indonesia that have a number of potential tourist villages. One way to develop a tourist village can be done by incorporating elements of gastronomy. The purpose of this research is to prioritize the culinary field which is also part of the tourism sector, which is increasingly being improved in tourist villages, by utilizing gastronomy. However, culinary in this tourist village is not only about cooking, but more than that there are many additional, more complete knowledge in the culinary field itself. This study uses qualitative methods coupled with data collection methods through interviews. By interviewing several tourist villages and the ICA (Indonesian Chef Association) community directly. The findings from his research are the importance of the ICA community contributing directly to gastronomy in Indonesian tourist villages, especially Bandung City. This research is expected to support the sustainable development of tourist villages in the city of Bandung. And become a new innovation for a number of potential tourist villages